(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Due to increased maintenance and rehabilitation actions, significant volumes of Reclaimed Asphalt Pavement (RAP) are left in stockpiles. Replacing aggregate in Portland Cement Concrete (PCC) with additional RAP could help eliminate surplus RAP stockpiles and reduce PCC’s natural aggregate consumption, positively impacting the environment and the economy. This paper is a state-of-the-art review of the literature on using RAP to Roller-compacted Concrete pavement (RCCP). The potential of RAP aggregates has been assessed based on their characteristics and the optimum moisture content (OMC), maximum dry density (MDD), compressive strength, splitting tensile strength, flexural strength, modulus of elasticity, abrasion resistance, shrinkage, porosity, water absorption, and freeze-thaw of RCCP. The literature study illustrated how a low-density, smooth-textured hydrophobic asphalt covering surrounds RAP aggregates. potentially reducing the maximum dry density (MDD) and optimum moisture content (OMC) of RCCP mixtures. This asphalt layer could reduce RAP’s ability to bind with cement paste, reducing its strength properties. In addition, the hydrophobic nature of RAP may reduce porosity and water absorption. On the other hand, agglomerates and dust can have the reverse impact. Pavement application might be done with a lower replacement of RAP (less than 50%) without affecting the pavement’s strength, porosity, or water absorption. However, Increasing the replacement of RAP aggregate may not be conducive to mechanical performance, but it has the potential to enhance the toughness and energy absorption capacity of pavements.